Electrical properties of dry soil under high impulse currents - MOHAMADNOR, N; RAMLI, A (ELSEVIER SCIENCE BV, 2007)
To date, no publication has been made on dry soil characteristics under high impulse current conditions. This is because, no conduction current was detected in the dry soil, which may be due to high bulk resistance in the dry soil, limitations in the impulse generator and in the transducers adopted during the tests. In this study, however, for the first time, conduction current in dry soil was observed, despite the high resistivity of the dry soil and the large equivalent resistance of the test cell. It would be expected that the ionization process occurred mainly in the dry soil, since there is no water path in dry soil, and the voids are filled mainly with air. The goal of this paper is to contribute a better understanding of the ionization and thermal phenomena that occur in dry soil. (c) 2006 Elsevier B.V. All rights reserved.